Attitudes Toward Suicide among College Students - Elsa Nur Laela Sari; Aat Sriati; Efri Widianti (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Suicide is a problem in the world and the case was incrased. College students are included in the vulnerable population of suicide (15-29 years old) with a lot of problems that cause stress,anxiety and depression and can build attitudes towards suicide. Attitude correlates with suicidal behavior. The purpose of this study was to determine the attitudes of college students towards suicide. This research was used descriptive quantitative mothod. The sample was determined by the Proportional Random Sampling technique and 393 respondents were obtained. Attitudes Toward Suicide(ATTS) questionnaire was used as instrumen in this study with a Cronbach’s Alpha value is 0,65. Univariate data analysis is performed by determining the mean for each item and then using a percentage to determine the frequency distribution. The results in this study showed that most respondents have a pro-preventive attitude as indicated by (96.7%) respondents agreed that suicide can be prevented and have a low permissiveness attitude or do not agree with suicide as indicated by (82.5%) respondents agreed that "Suicide never can be justified ". However, (57%) felt taboo and avoided talking about suicide. The conclusion of this study is that most respondents have a pro-prevention attitude and do not agree with suicide. However, respondents consider it taboo to talk about suicide.